Understanding the Drivers of Online Loan Usage in Fashion MSMEs: An Empirical Study in West Java - Apriliana, Tria; Gusni, Gusni; Iriani, Yani (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Access to finance for MSMEs is an important factor in supporting economic growth in Indonesia. Although MSMEs contribute significantly to GDP and employment absorption, they often face difficulties in obtaining funding from traditional financial institutions. With the advancement of information technology, fintech lending has become a popular alternative that offers quick, easy, and inclusive financing. However, the adoption of online loans by MSMEs has not been optimal. This study aims to analyze the factors influencing the intention to use online loans among fashion MSMEs in West Java. This research uses the Technology Acceptance Model (TAM) as the theoretical framework, with independent variables such as subjective norms, perceived behavioral control, financial literacy, risk perception, social influence, perceived ease of use, and perceived usefulness. Data were collected from 40 respondents using simple random sampling and analyzed using SEM-PLS. The results indicate that subjective norms and perceived behavioral control have a positive influence, while financial literacy and risk perception have a negative influence on the intention to use online loans. Social influence, perceived ease of use, and perceived usefulness do not have a significant effect. Limitations include a small sample size and a limited scope. Keywords: Online Loan; Msmes; Subjective Norms; Financial Literacy; TAM